T/V Pronouns and FTAs in the Works of Sir Thomas Malory: Medieval Politeness and Impoliteness in Directives, Expressives, and Commissives - Wiśniewska-Przymusińska, Malwina (Studia Anglica Posnaniensia, 2020)
Middle English second person pronouns thou and you (T/V) are considered to be among the means employed by medieval speakers to express their attitudes towards each other. Along with face-threatening acts, the use of these pronouns could indicate power relations or solidarity/distance between the interactants (Taavitsainen & Jucker 2003; Jucker 2010; Mazzon 2010; Bax & Kádár 2011, 2012; Jucker 2012). Using the tools available in pragmatic research, this paper attempts to provide an analysis of selected fragments from The Works of Sir Thomas Malory (Vinaver 1948 [1947]), analysed through the lens of Searle’s speech act theory (1969, 1976). The aim of this paper is to investigate whether the usage of T/V pronouns in polite or impolite contexts depends on the speech act in which they appear or not. Secondly, it looks at the presence of face-threatening acts (FTAs) and their potential influence on polite or impolite pronoun usage. Lastly, the analysis looks at the usage of FTAs within specific speech acts. The fragments used in this article were chosen from five chapters of Malory’s text: The Tale of King Arthur, Lancelot and Guinevere, The Morte Arthur, The Noble Tale, and Tristram de Lyones.